Reduction of Mutual Coupling between Closely Spaced Microstrip Antennas Arrays Using Electromagnetic Band-gap (2D-EBG) Structures - Ahmed Ghaloua; Jamal Zbitou; Larbi El Abdellaoui; Mohamed Latrach; Abdelali Tajmouati; Ahmed Errkik (Universitas Ahmad Dahlan, 2018)
Reducing mutual coupling is a key research area in design of compact microstrip antennas arrays. To minimize the overall size of the antennas arrays, the distance between them must be very small, as a result a strong mutual coupling is appears. Periodic structures can help to design a low profile of antennas arrays and enable to improve their performances by the suppression of surface waves propagation in a given frequency range. This paper proposes a novel configuration of mushroom-like electromagnetic band-gap (2D-EBG) structure created by microstrip technology placed between two antennas arrays to reduce the mutual coupling more than -33.24dB. When 13×2 EBG structures are used, the mutual coupling reduces to -59.36dB at the operation frequency 5.8GHz of the antennas arrays. A 26.12dB mutual coupling reduction is achieved, which proves that the surface wave is suppressed. The proposed configuration is designed, optimized, and miniaturized by using electromagnetic software CST Microwave Studio. The measured results show that there is a good agreement with the computed results.